Hotdog in bun: a recent technique for oophoropexy - Shah, Nitin H.; Joshi, Aditi V.; Belekar, Gitanjali (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Ovarian torsion is an acute gynaecological emergency. It may present at any age group, however it is more common in the reproductive years. The patient may present with a myriad of clinical features which are often non-specific posing a diagnostic dilemma. Ultrasonography is the best initial modality of imaging. Once diagnosed a surgical approach is the mainstay of treatment. Preservation of ovaries and preventing recurrence in young patients is crucial. We present a case of a young adolescent girl diagnosed with an ovarian torsion who was managed laparoscopically. Oophoropexy was done to avoid future recurrence by an emerging method called the “Hotdog in bun” technique.